PELAKSANAAN PRODUK PEMBIAYAAN MODAL USAHA TEMPE MELALUI AKAD MUSYARAKAH DI BSI BIREUEN - Syerly Nirwana (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2023)
This research is motivated by the development of Bank Aceh Syariah in providing business capital to its customers, one of which is by using musyarakah contracts and documentation. The results of this study explain that the financing mechanism with a musyarakah contract implements several stages, namely: Application Submission Stage, Document Verification Stage, Survey Stage, Analysis Stage, Akad Signing and Engagement Stage, Disbursement Stage, and Financing Monitoring Stage. Constraints in the application of musyarakah contract financing are several factors. The bank said that the customer's dishonesty and lack of understanding of the customer were obstacles in financing musyarakah contracts, the bank said that the problem was the lack of understanding of customers about musyarakah contracts, due to the lack of information and outreach about musyarakah financing to customers and the public.